R/V NATSUSHIMA NT07-12 Cruise Data - JAMSTEC (JAMSTEC, 2007)
[CRUISE DATA] This site includes a cruise dataset acquired in NT07-12 on R/V NATSUSHIMA from 2007-06-28 to 2007-07-02.
Observation contents: Expendable Bathythermograph
Keywords: Research cruise; R/V NATSUSHIMA; oceans